Comparative disinfection efficacy in aquaculture: novel methylene bis(thiocyanate) vs. conventional trichloroisocyanuric acid against Aeromonas hydrophila - Yang, Guang; Huang, Ying; Ma, Ning; Li, Kai; Wang, Xiao-mei; Zhang, Lian-bo; Yang, Wen-bo; Zhang, Wan-li; Xia, Lei; Zhang, Hong-Yu; Yuan, Li-lai (Frontiers in Microbiology, 2025)
Aeromonas hydrophila is a major pathogen responsible for significant economic losses in global aquaculture. Inhibitory and bactericidal activities of seven disinfectants were tested against 10 aquatic pathogens, including A. hydrophila, A. veronii, A. salmonicida, A. sobria, Edwardsiella tarda, E. ictaluri, Pseudomonas aeruginosa, and Yersinia ruckeri. Minimal effective concentrations were determined via quantitative suspension tests, while a scale-trauma zebrafish model assessed in vivo protection. Methylene bis(thiocyanate) (MBT) exhibited the strongest antimicrobial activity, with minimum inhibitory concentrations and minimum bactericidal concentrations of 0.1–0.4 mg/L and 0.2–0.8 mg/L, respectively. At 0.01 mg/L, MBT achieved a 3-log pathogen inactivation, equivalent to 0.2 mg/L Trichloroisocyanuric acid (TCCA). In vivo, 0.01 mg/L MBT provided 100% protection in zebrafish after 6 and 12 h exposure, whereas 0.2 mg/L TCCA yielded 95.83 ± 3.61% survival after 1 h. The safe concentrations of MBT and TCCA for zebrafish were 0.0364 and 0.0677 mg/L, respectively. The results showed that both TCCA and MBT effectively controlled A. hydrophila infection; however, MBT demonstrated greater potential for aquaculture applications due to its lower effective concentration (0.01 mg/L) and reduced sensitivity to interference from organic matter. In addition, this study presents a systematic protocol for evaluating the efficacy of disinfectants.